2007
DOI: 10.1152/ajpheart.00675.2006
|View full text |Cite
|
Sign up to set email alerts
|

The A2a/A2b receptor antagonist ZM-241385 blocks the cardioprotective effect of adenosine agonist pretreatment in in vivo rat myocardium

Abstract: Lasley RD, Kristo G, Keith BJ, Mentzer RM, Jr. The A2a/A2b receptor antagonist ZM-241385 blocks the cardioprotective effect of adenosine agonist pretreatment in in vivo rat myocardium. Am J Physiol Heart Circ Physiol 292: H426 -H431, 2007. First published September 15, 2006; doi:10.1152/ajpheart.00675.2006.-There is increasing evidence for interactions among adenosine receptor subtypes in the brain and heart. The purpose of this study was to determine whether the adenosine A 2a receptor modulates the infarct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…‫,ء‬ P Ͻ 0.05, treated versus control. or ischemic preconditioning (35-50%) (Yellon et al, 1992;Lasley et al, 2007). This is also the first study that has shown cross-talk between PAR4 and adenosine receptors during myocardial ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 81%
“…‫,ء‬ P Ͻ 0.05, treated versus control. or ischemic preconditioning (35-50%) (Yellon et al, 1992;Lasley et al, 2007). This is also the first study that has shown cross-talk between PAR4 and adenosine receptors during myocardial ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 81%
“…We (19,33) have previously reported that antagonism of adenosine A 2A and/or A 2B receptors with ZM-241385 blocked adenosine A 1 receptor agonist-mediated infarct size reduction in intact rats. Urmaliya et al (39) reported that A 1 receptormediated protection of H9c2(2-1) cells during simulated ischemia was blocked by both A 2A and A 2B receptor antagonists.…”
mentioning
confidence: 88%
“…We (19,33) The purpose of this study was to determine whether the cardioprotective effects of adenosine A 1 receptor activation before ischemia and at the onset of reperfusion are modulated by A 2A and/or A 2B receptors. Experiments were conducted in isolated perfused hearts of wild-type (WT), A 2A KO, and A 2B KO mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there have also been reports showing both anti-inflammatory (8,26) and anti-infarct (1) effects of A 3 adenosine receptor activation. Nevertheless, the cardioprotective effects of adenosine during reperfusion injury appear to be mediated at least in part by A 2A receptor activation (2,13,15,18). Activation of A 2A receptors results in increased intracellular adenosine 3Ј,5Ј-cyclic monophosphate (cAMP) concentration, resulting in activation of protein kinase A and inhibition of multiple steps in the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%